MODERN DIGITAL TECHNOLOGIES IN COMPOSITION EDUCATION AND PEDAGOGICAL APPROACHES - Saitkulova Oltinoy Juraboy kizi; Nusharov Bobir Bolbekovich (Web of Journals Publishing, 2025)
This article examines the application of digital technologies in composition education to enhance students’ creative thinking, visual perception, and technical literacy. The importance of improving teachers’ professional competence and implementing innovative pedagogical methods is also highlighted.
Keywords: Composition, digital technologies, pedagogical innovation, visual perception, 3D modeling, students’ creative thinking, art education, creative potential.